The Influence of Educational Background and Ethics on Audit Quality: A Case Study in PWC, EY, Deloitte, and KPMG - Putri Puspitosari, Desi Kristin (Jurnal Ilmiah Mahasiswa FEB, 2019)
Good audit quality is determined by the quality of human resources as well. So from this study will look at the basic things that must be owned by auditors namely education and ethics. This study is intended to determine the effect of educational and ethical backgrounds on audit quality. Respondents in this study were auditors working in Big4 KAP, PWC, Deloitte, EY and KPMG. This study uses primary data collected using a questionnaire. Collecting data using convenience sampling technique. One hundred and twenty questionnaires were distributed to the Big4 KAP where each KAP received 30 questionnaires. From the questionnaire distributed which can be processed are 74 questionnaires. The data analysis technique used is Multiple Linear Regression. The results show that the Education Background and Ethics influence positively Audit Quality.Keywords: Audit Quality, Educational Background, and Ethics.